2022
DOI: 10.20377/jfr-717
|View full text |Cite
|
Sign up to set email alerts
|

The division of child care during the coronavirus crisis in Germany: How did short-time work affect fathers' engagement?

Abstract: Objective: This paper examines how participation in the short-time work scheme affected the gendered division of child care during the COVID-19 crisis in Germany. Background: Short-time work (Kurzarbeit) has been one of the main policies used to combat the economic and labour market repercussions of the coronavirus pandemic in Germany. We examine whether and, if so, how the growing prevalence of short-time work has affected care patterns. Method: We use data from the IAB-HOPP, a longitudinal study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…10 In fact, prior research for Austria shows that throughout 2020, the crisis had affected women's and men's employment to a rather similar degree: Compared to 2019, employment declined by about 2% with negligible gender differences ) and only slightly more men than women were on shorttime work during the year 2020 (Steiber et al 2021: 5; for similar results in the German context, see Naujoks et al in this Special Issue). Some have argued that the COVID-19 crisis led to a re-traditionalisation of gendered employment and that mothers in particular faced a greater risk of job loss or hours reductions compared to men and childless women (e.g., Hipp & Bünning 2021;Hanzl & Rehm 2021, but Knize et al 2021. Evidence for the United States (Lofton et al 2021;Landivar et al 2020) shows that in this crisis mothers' employment has declined more steeply than fathers' while the recovery of jobs has been faster for men and childless women than for mothers.…”
Section: Parental Employmentmentioning
confidence: 99%
See 1 more Smart Citation
“…10 In fact, prior research for Austria shows that throughout 2020, the crisis had affected women's and men's employment to a rather similar degree: Compared to 2019, employment declined by about 2% with negligible gender differences ) and only slightly more men than women were on shorttime work during the year 2020 (Steiber et al 2021: 5; for similar results in the German context, see Naujoks et al in this Special Issue). Some have argued that the COVID-19 crisis led to a re-traditionalisation of gendered employment and that mothers in particular faced a greater risk of job loss or hours reductions compared to men and childless women (e.g., Hipp & Bünning 2021;Hanzl & Rehm 2021, but Knize et al 2021. Evidence for the United States (Lofton et al 2021;Landivar et al 2020) shows that in this crisis mothers' employment has declined more steeply than fathers' while the recovery of jobs has been faster for men and childless women than for mothers.…”
Section: Parental Employmentmentioning
confidence: 99%
“…Our study has an explicit focus on the main drivers (i.e., labour market shocks such as job loss or short-time work) and extent of financial hardship that was experienced by families in Austria during the first ten months of the COVID-19 crisis. Gendered experiences within households are outside the scope of this study (see Berghammer 2021 andNaujoks et al 2021 in this Special Issue for studies on the impact of the pandemic on the division of care work within families).…”
Section: Introductionmentioning
confidence: 99%
“…Fathers who participated in this programme engaged in more housework and childcare, particularly fathers with low or medium educational level. 54 In the USA, parents who reported having no help in household and childcare labour were more likely to reduce paid work hours or completely drop out of the paid workforce. Thus, shared parenting may support workforce participation, with economic benefit for the family.…”
Section: Discussionmentioning
confidence: 99%
“…Sevilla and Smith 56 ), multiple reports indicate more equitable sharing of household and childcare labour by parents in diverse cultures during the COVID-19 pandemic. 54,55,[57][58][59] When the division of household labour and childcare was perceived to be more equitable, mothers reported fewer relationship problems 60 and better coping skills. 61 Perhaps counterintuitively, we found that shared parenting had the largest effect on the mental health of parents with adolescent children compared with parents with younger children.…”
Section: Shared Parentingmentioning
confidence: 99%
See 1 more Smart Citation